3-D Analytical Model of Racetrack HTS Coil Subject to Travelling Magnetic Fields - Zhao, Zhengwei; Xu, Shuai; Liu, Kang; Yang, Wenjiao; Li, Jing; Ma, Guangtong (Journal of superconductivity and novel magnetism, 2021)
Magnetic levitation (maglev) train has the unique advantages of no-mechanical contact, high operating speed, and so on. All those advantages indicate the potential of maglev in the future ultra-high-speed ground transit, in which the high-temperature superconducting (HTS) linear synchronous motor (LSM) is essential because of its sample structure and excellent performance. HTS LSM is a typical application of racetrack HTS coil subject to travelling magnetic field. Motivated by an efficient method to promote the application of maglev, a 3-D analytical model combining the dynamic circuit theory and virtual displacement method was proposed for estimating the performances of racetrack HTS coil in LSM. To verify the proposed 3-D analytical model, the calculated open-circuit magnetic field and back electromotive force were compared with the numerical results of a 3-D finite element model in which the actual geometry of HTS LSM and the nonlinear conductivity of HTS tapes were taken into account. Based on the validated 3-D analytical model, the characteristics of HTS LSM was analyzed. The obtained results indicate that the validated 3-D analytical model could be a very efficient tool for the characteristic analysis and optimization of HTS LSM.